Disparities Old and New in US Mental Health during the COVID‐19 Pandemic. (30th November 2020) - Swaziek, Zachary; Wozniak, Abigail
Abstract: The COVID‐19 pandemic has reduced well‐being and economic security on a number of dimensions, likely worsening mental health. In this paper, we assess how mental health in the US population has changed during the pandemic. We use three large, nationally representative survey sources to provide a picture of mental health prior to and during the pandemic. We find dramatic but broad‐based declines in the level of mental health from pre‐pandemic baseline measures across both people and places. Rates of poor mental health have jumped roughly 25 percentage points, from a base of roughly one‐third. We document substantial disparities in mental health but show that the pandemic has generally preserved, rather than widened, these. Significant worsening in relative mental health among Hispanics and respondents aged 30 and older are exceptions. Consistent with an important role for pandemic‐specific shocks, We find that income loss, food insecurity, COVID‐19 infection or death in one's close circle, and personal health symptoms are all associated with substantially worse mental health. If anything, the decline in mental health is worsening as the pandemic wears on and is becoming less related to local COVID‐19 case rates.